КЛИНИЧЕСКИЕ ПРОЯВЛЕНИЯ ЮВЕНИЛЬНОГО ОСТЕОХОНДРОЗА У ДЕТЕЙ - Гузева, Валентина Ивановна; Гузева, Виктория Валентиновна; Гузева, Оксана Валентиновна; Разумовский, Михаил Анатольевич; Севрук, Елена Андреевна (FORCIPE, 2022)